The influences of brand image on perceived value and travelers’ purchase intention: Case of Sea Front Hotel DaNang - Nguyen, Thuc Hien (H. : ĐHQGHN, 2020)
This paper conducts a model to investigate the influence of brand image on perceived price, perceived quality, trust, perceived value and purchase intention. The indirect effects of brand image on purchase intention through perceived price, perceived trust, perceived value as mediators are also examined.